Assessment of Information Sharing on Adverse Drug Reactions by Community Pharmacies with Other Medical Institutions - Daisuke Kikuchi; Taku Obara; Aoi Noda; Gen Oyanagi; Mami Ishikuro; Kouji Okada; Nariyasu Mano (MDPI AG, 2022)
Widespread coordination and sharing of information regarding adverse drug reactions (ADRs) are important for drug safety assessment. However, the actual status of coordination and sharing of information on ADRs in community pharmacies remains unclear. Therefore, a survey was conducted at community pharmacies to analyze the status. In this cross-sectional study conducted from 31 March 2021 to 9 April 2021, a request letter with the uniform resource locator of the questionnaire form was sent to 302 community pharmacies affiliated with Tsuruha Holdings Inc., and the responses were obtained online. The response rate for the questionnaires was 80.8% (n = 244). In total, 20.9% of the community pharmacies provided information on patients' ADRs to hospitals or clinics prescribing drugs. None of the community pharmacies provided patient ADR information to other community pharmacies. Of the community pharmacies, 98.8% felt that insufficient information was available to monitor ADRs from hospitals or clinics prescribing drugs. For example, the name of the disease (67.6%), considered to be the most common information, was insufficiently provided. Overall, the existing system for providing information on ADRs between community pharmacies and other medical institutions is insufficient and needs to be developed further.